Designing parallel programs by the graphical language GRAPNEL - Kacsuk, Péter; Dózsa, Gábor; Fadgyas, Tibor (Microprocessing and microprogramming, 1996)
We propose a new visual programming language, called GRAPNEL (GRAphical Process's NEt Language), for designing distributed parallel programs based on the message passing programming paradigm. GRAPNEL supports graphically the Process Group abstraction and the automatic generation of several regular process topology based on predefined topology templates. Dynamic process creation and destruction are possible but can be applied only in a well structured manner. GRAPNEL is a hybrid language, where the communication related parts of the program are described using graphical symbols but textual descriptions are applied where they are more appropriate. The first prototype of the GRAPNEL programming environment uses the PVM as the basis of the message passing mechanism. Textual program parts can be written in standard C. Other message passing libraries (e.g. MPI) and ordinary textual languages (e.g. FORTRAN) are to be supported in the future.